1979
DOI: 10.1007/bf01064743
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and schizophrenia

Abstract: This artical begins with an introduction to social networks research and its practical importance in the understanding and treatment of schizophrenia, and concludes with a consideration of the experience, the phenomenology, of schizophrenia, from a social network point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
1
9
0
4
Order By: Relevance
“…A recent network study found many kin and friend relationships to be severed after only one hospital admission (Lipton, Cohen, Fischer, & Katz, 1981), a finding consistent with those of other studies demonstrating the longterm deleterious consequences of hospitalization on various adjustment indicators (Anthony & Farkas, 1982;Fontana & Dowds, 1975;Strauss & Carpenter, 1977;Test & Stein, 1978a). Similarly, length of hospitalization has been found to affect the patient's performance in numerous skill areas, as well as to reduce motivation and interest in social activities (Beels, 1979(Beels, , 1981Honigfeld & Gillis, 1967;Wing, 1962). Based on such research, from which one can conclude that deterioration of previous abilities and anhedonia are a function of acceptance of hospital life, length of hospitalization in the present model is suspected of influencing the network associations directly and indirectly through current resident skills and certain residential facility characteristics.…”
Section: Length Ofsupporting
confidence: 81%
“…A recent network study found many kin and friend relationships to be severed after only one hospital admission (Lipton, Cohen, Fischer, & Katz, 1981), a finding consistent with those of other studies demonstrating the longterm deleterious consequences of hospitalization on various adjustment indicators (Anthony & Farkas, 1982;Fontana & Dowds, 1975;Strauss & Carpenter, 1977;Test & Stein, 1978a). Similarly, length of hospitalization has been found to affect the patient's performance in numerous skill areas, as well as to reduce motivation and interest in social activities (Beels, 1979(Beels, , 1981Honigfeld & Gillis, 1967;Wing, 1962). Based on such research, from which one can conclude that deterioration of previous abilities and anhedonia are a function of acceptance of hospital life, length of hospitalization in the present model is suspected of influencing the network associations directly and indirectly through current resident skills and certain residential facility characteristics.…”
Section: Length Ofsupporting
confidence: 81%
“…Research has consistently reported smaller and poorer quality networks in people with severe mental health problems when compared to the general population [ 12 , 13 ]. It is often assumed that the size and quality of social networks diminish as a consequence of psychosis, with earlier theories proposing a ‘network crisis’ at first onset [ 14 , 15 ]. This has been contradicted by findings that network characteristics are relatively stable over the year following initial hospitalisation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Perform network assessments (Gottlieb & Coppard, 1987;Walsh, 1994); • Provide case management and linkages to social services (Pescosolido, Wright, & Sullivan, 1995), religious institutions (Walsh, 1994), and adult centers (Pickens, 1999); • Help clients create opportunities to meet new people (Katz, 1993;Walsh, 1994); • Provide referrals to medication groups and half-way houses (Beels, 1979); • Build new ties and strengthen existing ones (Tracy & Biegel, 1994); • Promote opportunities for bonding with network members (Ferris & Marshall, 1987); • Cultivate case consultation to assist clinical decision-making (Tracy & Wittaker, 1990); • Use multiple-family groups and psychoeducation (McFarlane et al, 1993(McFarlane et al, , 1995.…”
Section: Choosing An Interventionmentioning
confidence: 99%